2010
DOI: 10.3109/01443610903267457
|View full text |Cite
|
Sign up to set email alerts
|

Maternal risk factors and anaemia in pregnancy: A prospective retrospective cohort study

Abstract: Anaemia in pregnancy is still a concern during the reproductive period, as it is associated with increased maternal and perinatal mortality and morbidity. This study examined the maternal risk factors associated with increased prevalence of anaemia among antenatal and postnatal women. A prospective-retrospective cohort approach was carried out among 1,077 antenatal and 1,000 postnatal women. The haemoglobin was estimated using the cyanmethaemoglobin method. The maternal factors included were age, parity, educa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
1
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 9 publications
3
24
1
5
Order By: Relevance
“…Our study group showcased a 2.5% prevalence of anemia, lower than the one reported in other studies, 1,[16][17][18] with the exception of a Swiss study that also reported a low prevalence of IDA during pregnancy (3%). 19 The lower prevalence of IDA may be due to the demographic features of our study group, which only included women until the 20 th week of pregnancy.…”
Section: Discussioncontrasting
confidence: 76%
“…Our study group showcased a 2.5% prevalence of anemia, lower than the one reported in other studies, 1,[16][17][18] with the exception of a Swiss study that also reported a low prevalence of IDA during pregnancy (3%). 19 The lower prevalence of IDA may be due to the demographic features of our study group, which only included women until the 20 th week of pregnancy.…”
Section: Discussioncontrasting
confidence: 76%
“…A pesar de este avance, aún continúa como un problema de salud pública de moderada intensidad, según la clasificación de la Organización Mundial de la Salud (8) . Además, se debe tener en cuenta que la distribución de esta enfermedad responde a múltiples factores, encontrándose fuertemente asociada a variables sociodemográficas y territoriales (9)(10)(11) que, en un país tan diverso como el Perú, confluyen para generar marcadas disparidades y el mantenimiento de zonas con altas prevalencias de anemia gestacional. En tal sentido, la identificación de patrones de distribución territorial de esta enfermedad puede ser útil para identificar zonas de mayor concentración en donde se puedan proveer mayores cuidados materno-perinatales, así como la identificación y cuantificación de otras condiciones sociodemográficas y ambientales asociadas a la anemia.…”
Section: Introductionunclassified
“…As shown in Table 1, 420 pregnant women participated in this survey. About 50% of them were in the age [16][17][18][19][20][21][22][23][24]. The majority of the pregnant women were housewives (96.9%), and most of them were urban (56.7%), with no formal education (57.4%).…”
Section: Discussionmentioning
confidence: 99%